Javanese language host training for village officials in Panggungharjo Village, Bantul Regency - Aryanto, Aris; Santosa, Eko; Qurniawati, Zuly; Setyowati, Herlina (Community Empowerment, 2021)
The use of the Javanese language in daily communication, especially in meeting activities and ceremonial events, is still not properly used. In fact, Javanese is the mother tongue. In addition, there is still a lack of public knowledge, especially for village officials regarding the use of the Javanese language properly and correctly. Observing the existing condition, it is necessary to have training activities to become a master of ceremony (MC) in Javanese. The purpose of the Javanese MC training activity for village officials is to provide skills and mastery of appropriate Javanese grammar in daily communication. This training activity was carried out using lecture and practical methods. The Javanese MC training activities for village officials in Panggungharjo Village can take place well, smoothly and as expected. The motivation of village officials to practice being an MC in Javanese is getting stronger and better.